The articulation between innovation and competences anchored by knowledge management aiming sustainable competitive advantage - Ribeiro, Jurema Suely de Araújo Nery; SOARES, MARCO ANTÔNIO CALIJORNE; Abranches, Paulo Henrique Jurza; Ziviani, Fabricio (Faculdade de Filosofia e Ciências, 2018)
Organizations while seeking to establish higher standards of performance and sustainable competitive advantage have been stimulating a critical reflection about the factors that affect the performance of the individual and of the organizations. Knowledge became one of the main organizational competitive factors and knowledge management could contribute as a enhancer of organizational results. This paper aims to demonstrate the importance os knowledge management practices as a promoter of sustainable competitive advantage, considering its influence in the organizational context. For this, this theoretical paper has realized a brief literature revision in the knowledge management and sustainable competitive advantage fields, presenting concepts and approaches, in order to understand the interaction of these constructs with competence and innovations constructs. The results signalized that the comprehension of the relations between competences and innovation, anchored by knowledge management, is the assurance of the adequate conduction of the mechanisms through the competitive advantage could be sustained. For demonstrating this, it was proposer a systematized model to knowledge management and competitive advantage, structured with competence and innovation constructs. .